Bay Leaf Extract (Eugenia polyantha wight) to Reduce Plaque Index - Muhammad Saleh; Sainuddin Sainuddin; Bahtiar Bahtiar (Alliance oh Health Activists (AloHA), 2021)
Mouthwash from natural ingredients is more efficient, environmentally friendly, easy to obtain, and has minimal side effects, one of which is bay leaf. This study aims to analyze the effect of gargling using bay leaf extract (Eugenia polyantha wight) on the reduction of plaque index. This study was a literature review. Information obtained from text books, journals, books and other literature (8). The information is collected and processed by the steps of editing, organizing and interpreting. Based on the results of the study, it can be concluded that gargling using bay leaf extract can reduce plaque index because bay leaves contain flavonoids, essential oils, eugenol and tannins which have anti-inflammatory and anti-microbial effects. Keywords: bay leaf (Eugenia polyantha wight); gargling; plaque index